Influence of age, gender and delay on overtaking dynamics. Issue 2 (1st June 2013) - Llorca, Carlos; García, Alfredo; Moreno, Ana Tsui; Pérez‐Zuriaga, Ana María
Abstract : Overtaking is one of the most dangerous manoeuvres on two‐lane rural highways. The most influential factors are related to drivers, so ITS and assistance systems are not yet common. This research is based on experimental data of overtaking manoeuvres collected using an instrumented passenger car, equipped with four cameras, laser rangefinders and a global positioning service (GPS) tracker. This vehicle was driven along four different road segments in the surroundings of Valencia (Spain) at a speed slightly slower than the operating speed of each segment. Overtaking time and speeds were measured. Unlike previous work, the influence of human factor was also considered. Age and gender of overtaking driver, as well as time spent following were used to characterise this influence. More than 200 manoeuvres were recorded and the influence of driver characteristics and delay on gap acceptance, manoeuvre duration and speed differences have been analysed. Results show differences in behaviour between age and gender groups, since young male overtaking drivers have shown a more aggressive behaviour. Overtaking times were around 1 s lower than other drivers, whereas average speed difference was 4 km/h higher. Collected data and their analysis have provided a basis to review design criteria and to develop future assistance systems.